Noteworthy trends in maladaptive coping strategies and hindrances to help-seeking behaviour among adolescents living in Malaysia’s People’s Housing Project (PPR) during the COVID-19 pandemic: A qualitative study - Siti Nur Farhana Harun; Noorlaile Jasman; Feisul Mustapha; Norrafizah Jaafar; Siti Nadiah Busyra Mat Nadzir; Zanariah Zaini; Manimaran Krishnan; Ponnusamy Subramaniam (PLoS ONE, 2025)
Background COVID-19 has greatly affected the population, especially those in the low socio-economic group, including residents of the People’s Housing Project (PPR) in Malaysia. Adolescents residing in PPR communities are among the most vulnerable groups of young people in urban areas, given their pre-existing conditions of vulnerability, face even greater challenges due to the pandemic. Understanding their mental health and coping strategies is vital to grasp how the pandemic impacts their well-being. Hence, this study aims to explore the coping strategies and barriers to help-seeking behaviour among adolescents living in the Malaysia’s PPR communities, focusing on the unique mental health challenges exacerbated by the COVID-19 pandemic. Given the socio-economic vulnerabilities and the heightened mental health challenges during the pandemic, this study provides critical insights into how adolescents in PPR communities navigate psychological distress and mental health support. Methods This qualitative study used a phenomenological research design and was conducted from January to December 2022, involving 47 adolescents aged 10 to 17 years old from 37 PPRs in the Klang Valley. Participants were recruited using the purposive sampling method as this study purposely selected adolescents with moderate, moderately severe, and severe for PHQ-9 and/or moderate and severe for GAD-7 based on the screening. Participants who agreed to participate were recruited (with consent from parents/guardians) and interviews were set at the participants’ convenience. Data were collected using a semi-structured interview guide to conduct the in-depth interviews (IDI). After each IDI session, the recorded interviews were transcribed. Data from the voice recorder were stored on a password-protected computer, and participants’ names were replaced with specific codes to ensure confidentiality. The researchers coded all transcripts independently. The transcripts were analysed inductively using a thematic approach to identify recurring themes. Results From the 37 PPRs, 194 adolescents were identified as having psychological distress based on the screening. Among them, 47 agreed to participate in the IDIs, which revealed that these adolescents utilized mainly maladaptive coping strategies, such as avoidance (cognitive distancing, externalization, and internalization), self-harm, vaping, and smoking to deal with stressors related to COVID-19. As for hindrances to help-seeking, three themes were identified such as lack of trust, perceived ineffectiveness of support, and personality. Conclusion Psychological distress among adolescents was prevalent during the pandemic, and they faced hindrances in seeking help. Coping strategies have been identified to help adolescents manage their psychological distress during the pandemic. It is concerning that some had resorted to maladaptive coping mechanisms. These findings emphasized the need for targeted mental health interventions and support systems tailored to vulnerable communities. These interventions could inform policies aimed at strengthening mental health services, fostering better coping strategies and promoting help-seeking behaviours among adolescents in socio-economically challenged communities.